Socio-economic and cultural characteristics of the peasant families from Mantaro Valley between 1975 and 2015 - Tello Yance, Filoter (2018)
The present investigation arose to answer the problem: what are the socio-economic and cultural characteristics of the peasant families from Mantaro valley in 1975, and after the agricultural technological transfer and innovation, in 2015? The objective was to compare the socio-economic and cultural characteristics of the peasant families from Mantaro valley in 1975, and after the agricultural technological transfer and innovation, in 2015. The following hypothesis was put forward: the socio–economic and cultural characteristics of the peasant families from Mantaro valley in 1975, and after agricultural technology transfer and innovation, in 2015, show significant changes in socio–economic conditions, animal husbandry, crops and cultural patterns. In the development of the research work, it was used the scientific method, descriptive research level, with a descriptive comparative design. The population was constituted by 73 357 producers who are heads of familiy from Mantaro valley (four provinces and 76 districts), beneficiaries of the agricultural technological transfer and innovation from the state and private sector and/or through their own resources. The technique was the survey, and the instrument, the questionnaire. In the statistical analysis of the data obtained, the chi–squared test was used for the homogeneity of the samples, comparing the percentages from 1975 and 2015, at a 95% of statistical confidence.   DOI: https://doi.org/10.31876/sl.v2i1.9